A kinetic performance of Cross-Linked Enzyme Aggregates (CLEA)-amylase from Zophobas morio - Easa, Muhammad Noor; Yusof, Faridah; Abd Halim, Amanatuzzakiah (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Many studies have been done on various species of insects to investigate their potential use in industries. This is because insects have high protein content which could be further manipulated. Due to its eating habit, Zophobas morio larvae, also known as super mealworm has been shown to have high amylase activity. In this study, amylase from super mealworm has been immobilized via Cross-Linked Enzyme Aggregates (CLEA) technique and its kinetic performance, evaluated. CLEA is one of the best immobilization method with respect to enzyme stability and reusability. Kinetic performance of both free and CLEA-amylase were evaluated based on the Michaelis-Menten model. Results obtained based on Hanes-Woolf, Lineweaver-Burk, Eadie-Hofstee and Hyperbolic Regression plots showed that the kinetic parameters, Vmax and KM, changed upon immobilization. For CLEA-amylase, Hanes-Woolf plot showed the best-fitted model based on R2 with Vmax= 1.068 mM/min and KM= 0.182 mM, however, Lineweaver-Burk plot was used to obtain the kinetic parameters for free amylase, with Vmax and KM of 17.230 mM/min and 2.470 mM, respectively. Thus it is observed that upon immobilization, Vmax for amylase dropped appreciably, however, much lower substrate concentration is needed to saturate the enzymatic sites to reach its maximum catalytic efficiency. The result from this study might open the new path in discovering the potential use of insects in industrial applications, for example, making use of the recovered enzymes in the detergent industry.